Arsenic in Indo- Gangetic Plain of India: A Review - Sharma, Vivek Kumar; Rai, V. K. (National Geographical Journal of India, 2022)
India is a country of different physiographic regions. Indo-Gangetic Plain (IGP), also known as “Great Plains” in one of the main physiographic part of India. IGP is also a great reservoir of fresh ground water.Rapid growth of population,urbanization,industrilisation and over- exploitation of ground water is now creating a critical scenario for human health as increasing Arsenic quantity in groundwater of IGP. West Bengal,Bihar and Uttar Pradesh (Parts of IGP),have maximum Arsenic contamination.There are 79 blocks in 8 districts of West Bengal,57 blocks in 15 districts of Bihar and 45 blocks in 9 districts of U.P., are affected by the Arsenic contamination. Arsenic contaminatioin can be reduce by using surface water sources,tapping alternate aquifer and rain water harvesting.There is a need to aware the community about Arsenic and its related problems.There is a need of high technology and improved research for knowing the exact sources and mechanism of Arsenic mobility in the aquifers of IGP. This paper is chiefly an overview of Arsenic contamination in IGP regions of India (West Bengal, Bihar and Uttar Pradesh), based on secondary data, previous surveys and works done on it by several Govt. agencies and scholars